2017
DOI: 10.1002/jmri.25915
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal assessment of rabbit renal fibrosis induced by unilateral ureteral obstruction using two‐dimensional susceptibility weighted imaging

Abstract: 2 Technical Efficacy: Stage 1 J. Magn. Reson. Imaging 2018;47:1572-1577.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…The ability of SWI in noninvasive measurement of renal fibrosis has been shown in a rabbit model of UUO. 150,151 By incorporating sophisticated mathematical analysis, quantitative susceptibility mapping can be used to extract susceptibility maps from susceptibility-weighted images. Xie et al demonstrated a good sensitivity of high-resolution quantitative susceptibility mapping in detecting renal fibrosis in fixed kidneys of mice deficient for angiotensin receptor type-1.…”
Section: Other Mri Techniquesmentioning
confidence: 99%
“…The ability of SWI in noninvasive measurement of renal fibrosis has been shown in a rabbit model of UUO. 150,151 By incorporating sophisticated mathematical analysis, quantitative susceptibility mapping can be used to extract susceptibility maps from susceptibility-weighted images. Xie et al demonstrated a good sensitivity of high-resolution quantitative susceptibility mapping in detecting renal fibrosis in fixed kidneys of mice deficient for angiotensin receptor type-1.…”
Section: Other Mri Techniquesmentioning
confidence: 99%
“…Obstructive nephropathy may lead to Acute Kidney Injury (AKI) or Chronic Kidney Disease (CKD) [3,4,5]. CKD involves the progressive decrease in renal function and the alteration of renal structure lasting more than three months [6]. CKD is characterized by the loss of epithelial renal cells and their replacement with extracellular matrix (ECM) in the glomeruli and tubulointerstitium [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…CKD involves the progressive decrease in renal function and the alteration of renal structure lasting more than three months [6]. CKD is characterized by the loss of epithelial renal cells and their replacement with extracellular matrix (ECM) in the glomeruli and tubulointerstitium [5,6]. Patients with CKD are usually diagnosed after ECM accumulation has initiated [7] and show evidence of the effect of Reactive Oxygen Species (ROS)-induced damage in proteins, lipids and DNA [8].…”
Section: Introductionmentioning
confidence: 99%
“…After anesthesia, each rabbit was placed in the right lateral position. Consistent with previous literature, the operation was performed on the left kidney since the left kidney of rabbit is not hidden by the liver and ribs, making the surgery relatively easy. The left waist was incised by scalpel to 7 cm.…”
Section: Methodsmentioning
confidence: 99%